Lysyl Oxidase, Extracellular Matrix Remodeling and Cancer Metastasis - Xiao, Qian (Springer Netherlands, 2012)
Lysyl oxidase (LOX) family oxidases, LOX and LOXL1-4, oxidize lysine residues in collagens and elastin, resulting in the covalent crosslinking and stabilization of these extracellular matrix (ECM) structural components, thus provide collagen and elastic fibers much of their tensile strength and structural integrity. Abnormality in LOX expression and/or activity results in connective tissue disorders and fibrotic diseases. Despite LOX family oxidases have been reported to function as tumor suppressors, recent studies have highlighted the roles of LOX family oxidases in promoting cancer metastasis. LOX family oxidases are highly expressed in invasive tumors, and are closely associated with metastasis and poor patient outcome. Consistent to their roles in connective tissue homeostasis, LOX family oxidases expedite tumorigenesis and metastasis through active remodeling of tumor microenvironment. LOX family oxidases are also actively involved in the process of epithelial-mesenchymal transition (EMT), an event critical in cancer cell invasion and metastasis. In this review, we will summarize the recent progress on LOX family oxidases, with much of the focus on the roles and mechanism of LOX in tumor progression and metastasis.